A New Method for the Quantitative Assessment of Sustainable Development Goals (SDGs) and a Case Study on Central Asia - Yizhong Huan (Sustainability, 2019)
Regarding the sustainable development goals (SDGs) formulated by the United Nations (UN), how to effectively measure, assess and compare the progress and trends of these SDGs in different countries was the problem we wanted to address. Based on past quantitative assessments, this paper proposed a new methodological framework for SDG assessment and analysis, and used two typical Central Asian countries, Kazakhstan and Kyrgyzstan, as the sample area to test the framework. Our study chose 209 indicators and indicator sets, including 429 specific indicators and collected relevant indicator data for the two countries from 2000 to 2017, then proposed a new direction for the unification of indicator data as well as methods for normalization. Afterward, the scores of each goal and SDG performance were calculated. This analysis was also done innovatively using the Chow Test to conduct further analysis of the SDG performance. According to the assessment, over those 18 years, Kyrgyzstan’s SDGs had been performing poorly, especially the economic SDGs, while the performance of Kazakhstan’s SDGs had remained in constant fluctuation. It could be said that the SDG performance in Central Asia as a whole was not very optimistic. It required the devotion of greater efforts in the gathering of different types of indicator data because there were still gaps in data collection between countries as well as the missing of time-series data, which could challenge the indicator selection and further restrict the follow-up assessment and analysis. The assessment framework presented in this paper can be applied for assessing the long-term performance of national SDGs of different countries, helping analyze the internal relationship dynamic among and within countries, underscoring specific issues of sustainable development, assessing policy and selecting development models and directions.